Teaching With Technology: A Reflection on the Experience of Teaching With Computer Simulations - Maxwell Tsoka (E-Journal of Humanities, Arts and Social Sciences)
This paper describes the lived experience of one physical science teacher teaching with computer simulations in a rural school. The teacher’s goal was to improve the teaching and learning of the physical sciences, which has been identified as a challenge. The study adopted an auto-hermeneutical approach, a method of self-reflection and interpretation, which was deemed appropriate for this study, as it allowed the teachers to critically reflect on their own experiences and interpret the impact of computer simulations on their teaching. The study was also framed by constructivism. Data was gathered from the teacher’s reflective journals and focus group discussions with learners. A qualitative data analysis using the Colaizzi method was employed. The outcome revealed that the use of computer simulations is an odyssey, where actions were initiated that pacified teacher-dominated practices. One important transformation to learning was that computer simulations created a learning environment where learners did not passively accept but actively engaged with and believed the scientific ideas being taught. The ultimate goal of the transformation is the meaningful engagement of learners with content in a way that captures the zeitgeist of the 21st century.